Digital sports journalism - Lambert, Charles M.; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2019)
Digital Sports Journalism gives detailed guidance on a range of digital practices for producing content for smartphones and websites. Each chapter discusses a skill that has become essential for sports journalists today, with student-friendly features throughout to support learning. These include case studies, examples of sports journalism from leading global publications, as well as top tips and practical exercises. The book also presents interviews with leading sport and club journalists with wide-ranging experience at the BBC, Copa90, Wimbledon Tennis, the Guardian and BT Sport, who discuss working with new technologies to cover sports stories and events. Chapters cover:live blogging;making and disseminating short videos;working for a sports club or governing body;finding and transmitting stories on social media;podcasting;longform online journalism.The job of a sports journalist has altered dramatically over the first two decades of the 21st century, with scope to write content across a new variety of digital platforms and mediums. Digital Sports Journalism will help students of journalism and professionals unlock the potential of these new media technologies.
part, Digital content: first principles -- chapter Introduction -- chapter 1 Digital storytelling -- chapter 2 Getting set up -- chapter 3 Social media -- part, Match day: reporting a sporting event -- chapter 4 Live blogging -- chapter 5 Match reporting -- part, New techniques -- chapter 6 Attracting an audience -- chapter 7 Video-making -- chapter 8 Sports journalism and data -- part, 1 One-club journalism -- chapter 9 The club journalist -- chapter 10 The fan journalist -- part, Major projects: longer pieces of sports journalism -- chapter 11 Podcasts -- chapter 12 Longform journalism.
Keywords: LANGUAGE ARTS & DISCIPLINES / Journalism; Online journalism; Sports journalism